A design and analysis of a Darrieus Helical vertical axis wind generator by numerical simulation - Carpio, Jorge (2023)
This study addresses the problem of pollution and high energy demand in Peru, caused by population growth in the city. It proposes the use of renewable energy as a solution and seeks to analyze and design a vertical-axis wind turbine (VAWT) with variable rotor radius to evaluate its sustainability in Piura, Peru, as a renewable energy option. Climatological data from the Global Wind Atlas and the Capitán FAP Víctor Montes Arias Airport in Talara, Piura, were used. The blades were designed with aerodynamic models from SANDIA laboratories and analyzed using simulation software such as QBLADE and ANSYS FLUENT. The results indicate that the VAWT is efficient (Cp = 0.58) when the blades are contracted at 13.4 m/s. A closed-loop control is proposed to adjust the rotor radius with an anemometer. In addition, the airfoil behavior is observed by pressure and velocity plots in ANSYS FLUENT.